Pengaruh Penggunaan Aplikasi Digital Keterampilan kerja dan Budaya Kerja terhadap Efektivitas Kerja Pegawai UD. SUN FLOWER - Dewi Cantika Rahmawati; Anita Kartika Sari; Parwita Setya Wardhani (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research aims to analyze the use of digital applications for work skills, work culture and work effectiveness of UD employees. Sunflower. This research also aims to analyze the factors that have the most dominant influence on the use of digital applications among employees. This sampling method uses the Slovin formula method. This research was carried out using a quantitative approach, namely research that focuses on hypothesis testing using statistical method analysis tools. The sample used in this research was 70 respondents. The test tool used is a multiple linear regression analysis technique with the help of SPPS 29 software. From the results of the t test that has been carried out, Use of Digital Applications t count 2,269 > t table 1,996, Work Skills t count 2,416 > t table 1,996, Work Culture t count 2,597 > t table 1.996, which means that the variables Use of Digital Applications, Work Skills, Work Culture simultaneously influence Work Effectiveness. F-test results f-count 26.558 > 2.74, so it can be concluded that H4 is accepted, which means that the use of digital applications, work skills and work culture simultaneously have a significant effect on the work effectiveness of UD employees. Sunflower